Analisis Wacana Kritis Kampanye PDI-P di Media Sosial TikTok - Hardhiyyah Asrul, Hafizah; Delfia, Elly; Syaravina, Siti Awal Syaravina; Hidayah, Hanifahtul; Masitik, Siet (Universitas Andalas, 2025)
This research aims to observe and analyze the interests of certain parties behind the political discourse of the PDI Perjuangancampaign on TikTok social media. behind the political discourse of the PDI Perjuangan campaign on TikTok social media. The research uses Van Dijk's critical discourse analysis model. This research uses the virtual ethnography method with participatory observation on TikTok social media. There are three strategic stages in the framework of handling research problems (1) the data provision stage, (2) the data analysis stage, and (3) the data analysis stage. data, (2) the data analysis stage, and (3) the stage of presenting the results of the analysis. Researchers The researcher uses a sampling technique in the form of purposive sampling. Based on the macrostructure analysis, there is a topic element, namely the controversy arising from the use of PDI Perjuangan campaign jargon on social media platforms. on the TikTok social media platform. The jargon often often contains slogans that evoke the spirit of nationalism and nationalism. However, despite its popularity, various groups have criticized whether the use of this jargon is only a tool for the PDI Perjuangan campaign. this jargon is merely a political tool to gain sympathy or truly reflects a commitment to social and national issues. commitment to social and economic issues in society. society. The superstructure analysis identifies the text schema, which consists of consists of an introduction, body, and conclusion, all of which contain PDI Perjuangan slogans such as banteng pantang ciut, siap memenangkan pemilu and so on. so on. In the microstructure analysis, it involves the event setting, historical setting, intent, presupposition, and prejudice. historical setting, intention, presumption, nominalization, and metaphor.